Fundación del Partido Federal - Todd, Roberto H. (My University, 1941)
Acta de constitución del Partido Federal
Keywords: Partido Federal (Puerto Rico); Partido Republicano (Puerto Rico); Muñoz Rivera, Luis, 1859-1916; Hernández López, Juan; Román Manual C.; Siaca Pacheco, Ramón